PINK1/Parkin-Mediated Mitophagy Regulation by Reactive Oxygen Species Alleviates Rocaglamide A-Induced Apoptosis in Pancreatic Cancer Cells - Zhao, Chunle; He, Ruizhi; Shen, Ming; Zhu, Feng; Wang, Min; Liu, Yuhui; Chen, Hua; Li, Xu; Qin, Renyi (Frontiers in Pharmacology, 2019)
Pancreatic cancer (PC) is a highly lethal disease and effective treatment of PC patients remains an enormous challenge. Rocaglamide A (Roc-A), a bioactive molecule isolated from the medicinal plant Aglaia elliptifolia, has attracted considerable attention as a therapeutic option for numerous cancer treatments. However, the effects and underlying mechanism of action of Roc-A in PC is still poorly understood. Here we found that Roc-A inhibited growth and stimulated apoptosis by induction of mitochondria dysfunction in PC cells in vitro and in vivo. Moreover, Roc-A accelerated autophagosome synthesis and triggered mitophagy involving the PINK1/Parkin signal pathway. We also demonstrated that inhibition of autophagy/mitophagy can sensitize PC cells to Roc-A. Finally, Roc-A treatment results in a significant accumulation of intracellular reactive oxygen species (ROS) and pretreatment of cells with the ROS scavenger N-acetylcysteine reversed the apoptosis and autophagy/mitophagy induced by Roc-A. Together, our results provide novel insights into the mechanism of action of Roc-A. Our findings indicate Roc-A as a potential therapeutic agent against PC and suggest that the combination inhibition of autophagy and mitophagy may be a potential therapeutic strategy in PC.